Anna and the King Movie in the Form Address - Harsuni Winarti (Journal of English Language Teaching and Cultural Studies, 2018)
The purpose of the research is to analyze the term addresses which are used by the characters which come from different culture and different status in “Anna and the King” movie and to analyze the reasons of the characters of choosing particular addressing term in “Anna and the King” movie. In conducting of the research, the researcher uses the qualitative research. The data are collected from the dialogue on “Anna and the King” movie. The researcher observes the dialogue and writes down the manuscript which uses the form address. The data are collected by doing an observation on “Anna and the King” movie which will be played for several times and then write the data manuscript which are needed in conducting the research. There are some term of address based on Braun theory which are found in “Anna and the King” movie. The term of address are; Firstly, Kinship terms (KT) which shows blood relations and for affine. Secondly, General forms which need not be regarded as particular titles and are in common use. The third, the title is bestowed, achieved by appointment (such as Mr. Prime Minister). Next, the abstract noun which belong to some abstract quality of addressee (such as  Your Excellency, Your Honor, Your Grace), words for certain types of relationship (such as colleague, neighbor, friend) and lastly, the forms of address define addresses as father, brother, wife, daughter of someone else by expressing the addressee relation to another person (such as son of teacher).